CHARACTERISTICS OF HEMATOLOGICAL MANIFESTATIONS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: SINGLE CENTER EXPERIENCE - Gül Sandal Uzun (Hematology, Transfusion and Cell Therapy, 2025)
Objective: Systemic Lupus Erythematosus (SLE) is an autoimmune disease that manifests with various organ involvement, including hematological involvement. The objective of this study was to examine the demographic and clinical information, as well as the hematological involvement characteristics, of SLE patients. Methodology: The study was a single-center retrospective study. Patients with SLE who underwent complete follow-up visits were included in the study according to the classification criteria established by the American College of Rheumatology (ACR) and the Systemic Lupus International Cooperation Clinics (SLICC). A retrospective review of the patients' demographic and clinical information was conducted by examining the hospital's electronic record system. The clinical information, laboratory parameters, and SLE-specific treatments were documented. Patients were divided into sub-phenotypes according to organ involvement, and patients with hematologic involvement (anemia, leukopenia, thrombocytopenia, and splenomegaly) were identified. Statistical analyses were performed using SPSS version 26.0 (SPSS Inc., Chicago, IL, USA). The variables were calculated using visual (histogram and normality plots) and analytical methods (Kolmogorov-Smirnov) to determine whether they were normally distributed. Descriptive analysis was performed using mean ± Standard Deviation (SD) or median and Interquartile Range (IQR). Results: The study included 302 patients with SLE, 87 (34.7.8%) of whom had hematological manifestations. The mean age at diagnosis was 36.4 (±9.8). 237 (78.7%) of these patients were female. Clinical manifestations were observed among the patients, including skin involvement in (54.3%), articular involvement (48%), renal involvement in (26%). The ANA test was positive in 96.2% of patients with hematologic involvement. In addition, 34.7% had high anti-dsDNA autoantibodies and 33% had low C3 levels. Anemia was the most common hematological abnormality, affecting 55.7% of patients. The mean hemoglobin value was 9.7 mg/dL. Autoimmune hemolytic anemia was seen in 13.2% of patients. Thrombocytopenia was present in 9.2% of patients, and leukopenia in 12.2%. 57 (18.8%) SLE patients had secondary antiphospholipid antibody syndrome. 76.8% of patients received glucocorticoids and 81% received hydroxychloroquine treatment. 41% of patients received at least one steroid-sparing agent, including azathioprine, cyclophosphamide, mycophenolate mofetil, and rituximab. Conclusion: The hematologic manifestations of SLE should be evaluated and treated in order to provide a better outcome.